2022
DOI: 10.1177/14644207221130019
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation of AZ31B magnesium alloy in the preform and electropulsing treatment process

Abstract: Magnesium alloys exhibit poor formability at room temperature owing to their hexagonal close-packed crystal structure. In this study, a multi-step preform and electropulsing treatment method was applied to the plastic deformation of AZ31B magnesium alloy to improve its cumulative ductility. The mechanical properties, microstructure, and dislocation evolution were investigated using various parameters. The cumulative elongation of all specimens increased significantly, with the maximum approximately twofold hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Due to the increase in deformability, pressure treatment becomes possible without increasing the temperatures of brittle materials that are difficult to deform under normal conditions. A number of studies show that deformation with current can achieve better deformability of titanium alloys [ 61 , 62 ], magnesium alloys [ 16 , 27 , 63 , 64 ], aluminum [ 65 , 66 ], shape-memory alloys based on TiNi [ 67 , 68 ], and some other materials [ 69 ].…”
Section: Physical–mechanical and Technological Propertiesmentioning
confidence: 99%
“…Due to the increase in deformability, pressure treatment becomes possible without increasing the temperatures of brittle materials that are difficult to deform under normal conditions. A number of studies show that deformation with current can achieve better deformability of titanium alloys [ 61 , 62 ], magnesium alloys [ 16 , 27 , 63 , 64 ], aluminum [ 65 , 66 ], shape-memory alloys based on TiNi [ 67 , 68 ], and some other materials [ 69 ].…”
Section: Physical–mechanical and Technological Propertiesmentioning
confidence: 99%
“…Many experimental attempts 5,[8][9][10][11][12][13][14][15][16] have been made to understand the material behavior during uniaxial electric-assisted tensile (EAT) or compression tests. Okazaki et al 5 conducted EAT tests (pulsed DC, temperature maintained at ;20°C) on wire specimens of CP titanium and observed that stress-drop increased with an increase in the energy density and attributed the same to the EP effect.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 14 reported that yield strength decreased (16%) and elongation increased (33%) with electropulsing treatment (current density of 885 A/ mm 2 , 30 min duration) on the pre-strained (14%) AZ31B alloy (uniaxial tension test, temperature ;137°C) compared to that without electric aid and attributed the same to dislocation annihilation. Later the same group, 15 performed both prestrain (at 75% of elongation) and electro-pulsing treatment (current densities of 1000 and 1100 A/mm 2 , maximum duration of 11 min) repeatedly during uniaxial tension of AZ31B and observed that elongation increased with decrease in duration of treatment. Guo et al 16 conducted EAT (pulsed DC) of AZ31B alloy and observed that elongation increased by 41% compared to room temperature tests by suitable selection of pulse parameters (temperature reached is ;268°C and at which microstructural changes are reported).…”
Section: Introductionmentioning
confidence: 99%